Bio-based nanoemulsion formulations applicable in agriculture, medicine, and food industry - Jampílek, Josef; Kráľová, Katarína; Campos, Estefânia V. R. [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Springer, 2019)
Nanotechnology providing “a new dimension” accompanied with new properties conferred to many current materials is widely used for production of a new generation of agrochemicals; in medicine, it enables improved drug bioavailability, reducing undesirable side effects, minimizing non-specific uptake and specific targeting to certain target cells; while in food industry, it has great importance in food protection and biofortification of food with valuable ingredients. In bio-based nanoemulsions belonging to lipid nanocarriers, plant oils used for oil phase, emulsifiers, biosurfactants, cosurfactants, targeting ligands on the surface of nanoemulsion (e.g., folate), or encapsulated active ingredients are of natural origin. The biocomponents of such nanoemulsions show low toxicity to living organisms, could protect encapsulated compounds against degradation, ensure their sustainable release, and reduce the amount of active ingredient necessary for required effect. This chapter presents a comprehensive current overview of recent findings in the field of nanoemulsions and their utilization in agriculture and food industry, with the main emphasis on formulations encapsulating essential oils or plant extracts suitable as effective pesticide preparations as well as medicinal applications of bio-based nanoemulsions, where attention is paid to transdermal nanoemulsion formulations, the use of nanoemulsions in cancer therapy, and for pulmonary and ocular drug delivery. Nanoemulsions formulated with natural emulsifiers, biosurfactants, and biopolymers are presented, and bio-based nanoemulsions of essential oils and their constituents as well as nanoemulsions with encapsulated vitamins, fatty acids, and some bioactive compounds applicable in food products are discussed. Applications of nanoemulsions in edible coatings are outlined as well
Keywords: Nanoemulsions; Nanoformulations; Nanocomposites; Encapsulation; Drugs; Bioactive agents; Foodstuffs; Essential oils; Packaging materials